Light and temperature mediate algal stimulation of heterotrophic activity on decomposing leaf litter. (2nd January 2020) - Pope, Cody A.; Halvorson, Halvor M.; Findlay, Robert H.; Francoeur, Steven N.; Kuehn, Kevin A.
Abstract: Recent evidence suggests that periphytic algae stimulate plant litter heterotrophs (fungi and bacteria) in the presence of light, but few studies have tested whether this stimulation varies across gradients of light, which may covary with temperature. We exposed field‐conditioned Typha domingensis litter to fully‐crossed, short‐term gradients of temperature (15, 20, 25, and 30°C) and light (0, 25, 53, 123, and 388 µmol quanta m −2  s −1 ) and measured responses of litter‐associated algal, fungal, and bacterial production rates and β‐glucosidase, β‐xylosidase, and phenol oxidase enzyme activities in the laboratory. Increased light stimulated algal production rates, from immeasurable production under darkness to >200 µg algal C g −1 detrital C hr −1 at the highest light level, with the greatest light sensitivity and maximal photosynthetic rates at 25°C. In turn, increased light stimulated fungal production rates, especially at the two highest temperatures and most strongly at 25°C where light stimulated fungal production by a mean of 65 µg C g −1 detrital C hr −1, indicating 2.1‐fold stimulation by light. Bacterial production rates also responded to light, indicated by stimulation of a mean of 16 µg C g −1 detrital C hr −1 (1.6‐fold) at 15°C, but stimulation was weaker at higher temperatures. Enzyme activities increased strongly with elevated temperature but were not affected by light. Our experimental evidence suggests algae differentially stimulate litter‐associated bacteria and fungi in a light‐dependent manner that further depends on temperature. These findings advance understanding of the onset of algal stimulation of heterotrophy, including algal‐induced priming effects during litter decomposition, in response to common covarying environmental gradients subject to global change.